Sustainable Sewage Sludge Management and Resource Efficiency - Kiliç Taşeli, Başak (IntechOpen, 2020)
Creating decent living conditions for all people while decoupling economic growth from the increasing use of virgin resources and environmental impacts is the major challenge of this millennium. There are many approaches suggested for solving these problems, including changing consumption behavior from material products to services, finding technological solutions to create more closed loops for materials, and using fewer virgin resources and energy obtained from clean renewable sources. A main issue to address is sludge formation during wastewater treatment. As such, this book, over seven chapters divided into two sections, investigates the application of biosolids or sewage sludge together with possible resources for sustainable development. It also presents information on resource efficiency from a more complex perspective, looking at several resources and the causal links between them in order to point out new pathways towards a more sustainable use of resources.